Bilateral Mumps with Orchitis : A Case Report - Stefany Palyama; Retno Wisanti; Esthy Peospitaningtyas; Rusdian Niati Ningsih (International Medical Journal Corp. Ltd, 2025)
Background: Mumps or epidemic parotitis is an acute disease that often occurs in the salivary glands caused by infection from paramyxovirus . This virus spreads easily through airborne droplets and saliva. In the world, the incidence of mumps is 500,000 cases each year. Incomplete basic vaccination is one of the risk factors for mumps. Case Description: An 11-year-old male patient came with complaints of swelling in the right and left parotid glands. Initially the swelling was on the left. The patient had never been like this before. The patient's basic immunization history was incomplete. From physical examination, enlargement of both salivary glands was found. 2 weeks earlier at the patient's school, there were several students who experienced the same thing. The patient was referred to dr. Ramelan Central Naval Hospital after 5 days of hospitalization at the previous hospital and experienced swelling in the left scrotum. Discussion: Mumps often occurs in children aged 2-12 years. The occurrence of mumps can be caused by infection with the paramyxovirus virus which spreads from airborne droplets and salivary glands. One of the complications of mumps that often occurs in children is orchitis . Providing basic vaccines to children is one effort to prevent mumps. Bed rest, adequate fluid intake, and intravenous administration of NSAIDs and antibiotics can be options for mumps therapy. Conclusion: In this case, Mumps with Orchitis complications were diagnosed based on anamnesis, physical examination, and laboratory examination. Management of mumps is symptomatic. Incomplete basic vaccination is one of the biggest factors in the occurrence of mumps.